Backcrossing with marker assistance to introduce broad-spectrum bacterial leaf blight resistance in the Malaysian Elite Variety MR297 - Aljumaili, Saba Jasim; Rafii, Mohd Y.; Sakimin, Siti Zaharah; Ahmad, Khairulmazmi; Al-Jumaily, Abdulmajeed (Multidisciplinary Digital Publishing Institute, 2023)
A significant part of marker-assisted backcross breeding (MABB) is recurrent parent genome recovery (RPGR). The purpose of this study was to introduce MABB-mediated resistance genes against numerous bacterial leaf blight (BLB) pathogens. Here, we examine the introgression of four Xoo resistance genes to the high-yielding Malaysian MR297 lineage Xa21, xa13, xa5, and Xa4 from the IRBB60 lineage. To accomplish both foreground and background selection, we employed polymorphic functional linked markers to target genes and simple sequence repeat (SSR) markers. We used 83 of the 475 authorized polymorphic microsatellite markers to determine the proportion of RPGR in the chosen lines. According to the data, the RPGR at BC1F1, BC2F1, and BC2F2 are 81.94, 92.30, and 95.04, respectively. Incorporating the four BLB resistance genes into the newly created lines would result in long-lasting and comprehensive protection against BLB. Therefore, a resistant gene may be introduced into a population more quickly with MABB than through conventional breeding. All ten lines tested showed a significant level of resistance to BLB, with three lines displaying very high levels of resistance. Consequently, it was recommended that new lines should be used to produce commercially viable rice varieties.